Wear-resistant and corrosion-resistant polyethylene composite material for carrier roller and preparation method thereof

By using wear-resistant and anti-corrosion polyethylene composite material for stud rollers, the problem of wear and corrosion of plastic stud rollers under harsh working conditions is solved, and higher wear and corrosion resistance is achieved, extending service life and improving the stability and efficiency of the conveyor.

CN119684699AActive Publication Date: 2025-03-25SHANDONG KEWEIKE NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411972965.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Existing plastic rollers are prone to wear and corrosion under harsh working conditions, resulting in a shortened service life and affecting the operating stability and conveying efficiency of belt conveyors.

Method used

A wear-resistant and anti-corrosion polyethylene composite material for rollers is adopted, which consists of composite polyethylene, glass fiber, nanotitanium dioxide, graphene, toughening agent, antioxidant, ultraviolet absorber, silane coupling agent and wear-resistant anti-corrosion additive, and is prepared through a twin screw extrusion mechanism.

Benefits of technology

It significantly improves the wear resistance and corrosion resistance of the rollers, extends the service life, and ensures quality and quality, and improves the operating stability and conveying efficiency of the belt conveyor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219840550000111
    Figure BDA0005219840550000111
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a wear-resistant and corrosion-resistant polyethylene composite material for a carrier roller and a preparation method thereof. The polyethylene composite material is prepared from the following raw materials in parts by weight: 50-80 parts of compound polyethylene, 20-30 parts of glass fibers, 2-3 parts of molybdenum disulfide, 4-8 parts of ammonium polyphosphate, 2-5 parts of polyethylene wax, 5-8 parts of nano titanium dioxide, 0.8-1.5 parts of graphene, 5-8 parts of a toughening agent, 0.8-1.5 parts of an antioxidant, 0.5-1 part of an ultraviolet light absorber, 0.3-0.8 part of a silane coupling agent and 3-5 parts of a wear-resistant and anti-corrosion additive, the compound polyethylene is prepared by compounding high-density polyethylene with a melt index of 18 g / 10min and high-density polyethylene with a melt index of 0.8 g / 10min according to a mass ratio of (2-3): 1; the polyethylene composite material prepared by the invention not only has excellent wear resistance and mechanical properties, but also has excellent corrosion resistance, and the quality of the polyethylene composite material is ensured while the service life of the polyethylene composite material is prolonged to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a wear-resistant and corrosion-resistant polyethylene composite material for rollers and a preparation method thereof. Background Art

[0002] As a key component of belt conveyor, roller plays an important role in supporting the weight of conveyor belt and materials and reducing the running resistance of conveyor belt in many industries such as coal, mine, port, and electricity. There are two types of rollers: steel and plastic. Plastic rollers are widely used in the field of conveying systems because of their strong anti-adhesion ability and light weight. Although plastic rollers have excellent mechanical properties, their wear resistance and corrosion resistance are relatively insufficient and still need to be further improved. For example: plastic rollers are often faced with harsh working conditions during actual use, and the friction and wear caused by long-term contact with materials will cause serious damage to them. Furthermore, when plastic rollers are operated in a humid environment for a long time, their surfaces may be parasitized by microorganisms in the air, and the rollers will be corroded under the erosion of microorganisms, which will not only shorten the service life of plastic rollers, but also affect the overall operation stability and conveying efficiency of belt conveyors. Therefore, the present invention provides a wear-resistant and corrosion-resistant polyethylene composite material for rollers and a preparation method thereof to solve the above-mentioned technical problems! Summary of the invention

[0003] The purpose of the present invention is to provide a wear-resistant and corrosion-resistant polyethylene composite material for rollers and a preparation method thereof. The prepared polyethylene composite material not only has excellent wear resistance and mechanical properties, but also has excellent corrosion resistance, which prolongs its service life to a certain extent while also ensuring its quality.

[0004] To achieve the above object, the present invention provides the following technical solutions:

[0005] A wear-resistant and corrosion-resistant polyethylene composite material for a roller, the polyethylene composite material being composed of the following raw materials in parts by weight: 50 to 80 parts of compound polyethylene, 20 to 30 parts of glass fiber, 2 to 3 parts of molybdenum disulfide, 4 to 8 parts of ammonium polyphosphate, 2 to 5 parts of polyethylene wax, 5 to 8 parts of nano titanium dioxide, 0.8 to 1.5 parts of graphene, 5 to 8 parts of toughening agent, 0.8 to 1.5 parts of antioxidant, 0.5 to 1 part of ultraviolet absorber, 0.3 to 0.8 parts of silane coupling agent and 3 to 5 parts of wear-resistant and corrosion-resistant additives.

[0006] The compound polyethylene is compounded by high-density polyethylene with a melt index of 18 g / 10 min and high-density polyethylene with a melt index of 0.8 g / 10 min in a mass ratio of 2 to 3:1.

[0007] The antioxidant is selected from any one of antioxidants 1010, 1076, and 168.

[0008] The glass fiber is an alkali-free glass fiber with a diameter of 13 to 15 μm.

[0009] The ultraviolet absorber is selected from any one of ultraviolet absorbers UV-234, UV-120, UV-531, and UV-770.

[0010] The silane coupling agent is selected from any one of silane coupling agents KH550, KH560, and KH570.

[0011] Furthermore, the toughening agent is selected from any one of maleic anhydride grafted polyethylene, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-vinyl acetate copolymer.

[0012] Furthermore, the preparation method of the wear-resistant and anti-corrosion additive comprises the following steps:

[0013] Step 1, ultrasonically dispersing the pretreated spherical carrier in deionized water at a solid-liquid ratio of 30 to 60 g / L, then adding 30 to 50% of the grafting agent of the pretreated spherical carrier, 20 to 40% of 3-hydroxy-1,3,5-pentanetriic acid, 0.8 to 1.2% of p-hydroxyanisole, and 1 to 2% of ammonium chloride, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 100 to 120° C. for 20 to 40 minutes; after the reaction is completed, filtering, washing and drying the resultant components in turn, and storing and using the modified spherical carrier;

[0014] Step 2: Mix the irradiated modified Teflon particles with 0.8 to 1.2 times the mass of the modified spherical carrier and 3 to 5 times the volume of 90 to 95% ethanol aqueous solution, stir evenly, and then heat to 50 to 70° C., and then slowly drop 6 to 10% of the volume of the modified liquid into the obtained mixed solution; after the dropwise addition is completed, keep the mixture at 60 to 70° C. for 2 to 3 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, and then filter and vacuum dry them in turn to obtain a wear-resistant and anti-corrosion additive.

[0015] Furthermore, the preparation method of the pretreated spherical carrier is: add 3-8% of the mass of spherical carrier to the aqueous dispersion of spherical carrier with a concentration of 10-30g / L, perform ultrasonic dispersion for 20-30min, centrifuge and dry the obtained product components to obtain the pretreated spherical carrier.

[0016] Furthermore, the preparation method of the grafting agent is as follows: chitosan is added into isopropanol at a dosage ratio of 0.02 to 0.05 g / mL, and after ultrasonic dispersion for 30 to 50 minutes, trimethyl ammonium chloride glycidyl is added in an amount 3 to 5 times the mass of chitosan, and after mixing and stirring evenly, the mixture is kept warm for reaction at a temperature of 60 to 80° C. for 3 to 6 hours; after the reaction is completed, the grafting agent is obtained by washing and drying in sequence.

[0017] Furthermore, the preparation method of the modified liquid is: add 10-15% of the volume of vinyltrimethoxysilane to an ethanol aqueous solution with a volume concentration of 80-90%, mix and stir for 5-8 hours, and then adjust the pH to 3-3.5 with dilute hydrochloric acid to obtain the modified liquid.

[0018] Furthermore, the irradiation dose of the Teflon particles is 500-1000 KGy, the irradiation time is 5-10 days; and the particle size of the Teflon particles is 2-5 μm.

[0019] Furthermore, the preparation method of the spherical carrier is as follows: add a cerium nitrate aqueous solution with a volume of 3% to 6% and a concentration of 2 to 3 mol / L to a porous alumina microsphere aqueous dispersion with a concentration of 5 to 15 g / L, and then ultrasonically disperse it uniformly and keep it warm at a temperature of 120 to 160° C. for 10 to 20 hours; after the reaction is completed, the product components are naturally cooled to room temperature, and after centrifugal separation, the obtained filter cake is alternately washed with deionized water and anhydrous ethanol for 3 to 4 times; after washing is completed, it is vacuum dried to obtain a spherical carrier.

[0020] Furthermore, the preparation method of the porous alumina microspheres is as follows: aluminum hydroxide and deionized water are mixed in a mass ratio of 1:0.6-0.8, and after ball milling, 3-8% of ammonium bicarbonate and 2-3% of a 6-10wt% polyvinyl alcohol aqueous solution are added to the mixture, and the mixture is stirred at a rate of 1200-1500 r / min for 60-90 min; the obtained mixed slurry is spray-dried and then calcined at a temperature of 730-780°C for 1-2 h; after sintering is completed, the mixture is vibrated and sieved to obtain porous alumina microspheres with a particle size of 25-45 μm.

[0021] A method for preparing a wear-resistant and anti-corrosion polyethylene composite material for rollers, comprising the following steps: accurately weighing various raw materials required for preparing the polyethylene composite material, and putting them into a high-speed stirring device, mixing and stirring them uniformly, and transferring the obtained mixed material to a twin-screw extruder for basic granulation, and the obtained is the wear-resistant and anti-corrosion polyethylene composite material for rollers;

[0022] The parameters of twin-screw extrusion are set as follows: the temperature of the first section is 180-200°C, the temperature of the second to tenth sections is 200-240°C; the head temperature is 235°C, the main engine speed is 350-500rpm, and the feeding rate is 30-50rpm.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention uses aluminum hydroxide, ammonium bicarbonate and polyvinyl alcohol aqueous solution as raw materials to prepare porous alumina microspheres with porous spherical morphology. The porous alumina microspheres are then uniformly dispersed in a cerium nitrate aqueous solution, and after heat preservation reaction, a dense nano-cerium oxide film layer is deposited on the surface of the porous alumina microspheres and the inside of their porous structure to obtain a spherical carrier. The obtained spherical carrier is dispersed in deionized water after pretreatment with trimethyl ammonium glycidyl chloride, and then a grafting agent, 3-hydroxy-1,3,5-pentanetriac acid, p-hydroxyanisole and ammonium chloride are added thereto, and under the action of ammonium chloride, the grafting agent that reacts with 3-hydroxy-1,3,5-pentanetriac acid and is bonded is combined on the surface of the pretreated spherical carrier and its porous structure through a chemical reaction, and finally, under the mutual cooperation of the grafting agent, 3-hydroxy-1,3,5-pentanetriac acid and the nano-cerium dioxide film layer, the antibacterial performance of the wear-resistant and anticorrosive additive is significantly improved.

[0025] The obtained modified spherical carrier and Teflon particles are dispersed in an ethanol aqueous solution, and a modified liquid is dripped therein. After heat preservation reaction, the modified spherical carrier is bonded to the Teflon particles through vinyl trimethoxy silane, and finally a considerable amount of the modified spherical carrier is grafted on the surface of the Teflon particles, so that a wear-resistant anticorrosion additive is obtained. Since the prepared porous alumina microspheres are spherical structures, they can play a good "ball" effect, which makes them have excellent wear resistance. Furthermore, the presence of the nano cerium oxide film layer on its surface further improves its wear resistance. Since Teflon itself has good wear resistance, the modified spherical carrier is grafted on the surface of the Teflon particles through vinyl trimethoxy silane, and finally, under the mutual cooperation of the modified spherical carrier, the prepared wear-resistant anticorrosion additive has more excellent wear resistance.

[0026] In summary, using the wear-resistant and anticorrosive additive prepared by the present invention as a raw material for polyethylene composite materials can not only significantly improve the wear resistance of polyethylene composite materials and ensure their quality, but also significantly improve their antibacterial and anticorrosive properties, effectively reducing the probability of shortening the service life of polyethylene composite materials due to microbial growth and corrosion, and extending their service life to a certain extent. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A wear-resistant and corrosion-resistant polyethylene composite material for rollers, the polyethylene composite material consists of the following raw materials in parts by weight: 50 parts of compound polyethylene, 20 parts of glass fiber, 2 parts of molybdenum disulfide, 4 parts of ammonium polyphosphate, 2 parts of polyethylene wax, 5 parts of nano titanium dioxide, 0.8 parts of graphene, 5 parts of maleic anhydride grafted polyethylene, 0.8 parts of antioxidant 1010, 0.5 parts of ultraviolet absorber UV-234, 0.3 parts of silane coupling agent KH550 and 3 parts of wear-resistant and corrosion-resistant additives; wherein the compound polyethylene is compounded by high-density polyethylene with a melt index of 18 g / 10 min and high-density polyethylene with a melt index of 0.8 g / 10 min in a mass ratio of 2:1; the glass fiber is alkali-free glass fiber with a diameter of 13 μm.

[0030] The preparation method of the wear-resistant anticorrosion additive comprises the following steps:

[0031] Step 1, ultrasonically dispersing the pretreated spherical carrier in deionized water at a solid-liquid ratio of 30 g / L, then adding 30% of the grafting agent of the pretreated spherical carrier, 20% of 3-hydroxy-1,3,5-pentanetriic acid, 0.8% of p-hydroxyanisole, and 1% of ammonium chloride, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 100° C. for 40 minutes; after the reaction is completed, filtering, washing and drying the resultant components in turn, and storing the obtained modified spherical carrier for standby use;

[0032] The preparation method of the grafting agent is as follows: chitosan is added into isopropanol at a dosage ratio of 0.02 g / mL, and trimethyl ammonium chloride glycidyl is added after ultrasonic dispersion for 30 minutes with a mass of 3 times that of chitosan, and the mixture is mixed and stirred evenly and then kept warm for reaction at 60°C for 3 hours; after the reaction is completed, the grafting agent is obtained by washing and drying in sequence;

[0033] Step 2: Mix the irradiated modified Teflon particles with 0.8 times the mass of the modified spherical carrier and 3 times the volume concentration of 90% ethanol aqueous solution, stir evenly, heat to 50°C, and then slowly drop 6% of the modified liquid into the obtained mixed solution; after the dropwise addition is completed, keep the mixture at 60°C for 2h; after the reaction is completed, naturally cool the obtained product components to room temperature, and then filter and vacuum dry them in turn to obtain a wear-resistant and anti-corrosion additive;

[0034] The preparation method of the modified liquid is as follows: add 10% of the volume of vinyl trimethoxy silane to an ethanol aqueous solution with a volume concentration of 80%, mix and stir for 5 hours, and then adjust the pH to 3 with dilute hydrochloric acid to obtain the modified liquid;

[0035] The irradiation dose of the Teflon particles is 500 KGy, the irradiation time is 10 days, and the particle size of the Teflon particles is 2 μm.

[0036] The preparation method of the pretreated spherical carrier is as follows: add 3% of the mass of the spherical carrier to the aqueous dispersion of the spherical carrier with a concentration of 10g / L, perform ultrasonic dispersion for 20 minutes, centrifuge and dry the resulting components to obtain the pretreated spherical carrier.

[0037] The preparation method of the spherical carrier is as follows: add a 3% volume and 2 mol / L concentration of cerium nitrate aqueous solution to a 5 g / L concentration porous alumina microsphere aqueous dispersion, disperse evenly by ultrasonication, and then keep the mixture at 120°C for 10 hours; after the reaction is completed, naturally cool the product components to room temperature, and wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 3 times after centrifugal separation; after washing, vacuum dry the obtained filter cake to obtain the spherical carrier.

[0038] The preparation method of porous alumina microspheres is as follows: aluminum hydroxide and deionized water are mixed in a mass ratio of 1:0.6, and after ball milling, ammonium bicarbonate with a mass of 3% of aluminum hydroxide and 2% of a 6wt% polyvinyl alcohol aqueous solution are added, and the mixture is stirred at a rate of 1200r / min for 60min; the obtained mixed slurry is spray-dried and then calcined at a temperature of 730°C for 2h; after sintering is completed, it is vibrated and sieved to obtain porous alumina microspheres with a particle size of 25μm.

[0039] A method for preparing a wear-resistant and anti-corrosion polyethylene composite material for rollers, comprising the following steps: accurately weighing various raw materials required for preparing the polyethylene composite material, and putting them into a high-speed stirring device, mixing and stirring them uniformly, and transferring the obtained mixed material to a twin-screw extruder for basic granulation, and the obtained is the wear-resistant and anti-corrosion polyethylene composite material for rollers;

[0040] The parameters of the twin-screw extruder were set as follows: the temperature of the first section was 180°C, the temperature of the second to tenth sections was 200°C; the die temperature was 235°C, the main engine speed was 350rpm, and the feed rate was 30rpm.

[0041] Example 2

[0042] The preparation method of a wear-resistant and corrosion-resistant polyethylene composite material for rollers provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the wear-resistant and corrosion-resistant polyethylene composite material for rollers and the preparation method of the wear-resistant and corrosion-resistant additive are not completely the same. The specific composition of the wear-resistant and corrosion-resistant polyethylene composite material for rollers and the preparation method of the wear-resistant and corrosion-resistant additive in this embodiment are as follows:

[0043] A wear-resistant and corrosion-resistant polyethylene composite material for rollers, the polyethylene composite material consists of the following raw materials in parts by weight: 70 parts of compound polyethylene, 25 parts of glass fiber, 3 parts of molybdenum disulfide, 5 parts of ammonium polyphosphate, 3 parts of polyethylene wax, 6 parts of nano titanium dioxide, 1 part of graphene, 6 parts of maleic anhydride grafted polyethylene, 1.2 parts of antioxidant 1076, 0.8 parts of ultraviolet absorber UV-120, 0.5 parts of silane coupling agent KH560 and 4 parts of wear-resistant and corrosion-resistant additives; wherein the compound polyethylene is compounded by high-density polyethylene with a melt index of 18 g / 10 min and high-density polyethylene with a melt index of 0.8 g / 10 min in a mass ratio of 2:1; the glass fiber is alkali-free glass fiber with a diameter of 13 μm.

[0044] The preparation method of the wear-resistant anticorrosion additive comprises the following steps:

[0045] Step 1, ultrasonically dispersing the pretreated spherical carrier in deionized water at a solid-liquid ratio of 50g / L, then adding 40% of the grafting agent of the pretreated spherical carrier, 30% of 3-hydroxy-1,3,5-pentanetriic acid, 1% of p-hydroxyanisole, and 1.5% of ammonium chloride, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 110°C for 30 minutes; after the reaction is completed, filtering, washing and drying the resultant components in turn, and storing the obtained modified spherical carrier for standby use;

[0046] The preparation method of the grafting agent is as follows: chitosan is added into isopropanol at a dosage ratio of 0.03 g / mL, and trimethyl ammonium chloride glycidyl is added after ultrasonic dispersion for 40 minutes with a mass of 5 times that of chitosan, and the mixture is mixed and stirred evenly and then kept warm for reaction at 70°C for 5 hours; after the reaction is completed, the grafting agent is obtained by washing and drying in sequence;

[0047] Step 2: Mix the irradiated modified Teflon particles with 1 times the mass of the modified spherical carrier and 4 times the volume of 90% ethanol aqueous solution, stir evenly, heat to 60°C, and then slowly drop 8% of the modified liquid into the obtained mixture; after the dropwise addition is completed, keep the mixture at 65°C for 3 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, filter and vacuum dry them in turn to obtain a wear-resistant and anti-corrosion additive;

[0048] The preparation method of the modified liquid is as follows: add 15% of the volume of vinyl trimethoxy silane to an ethanol aqueous solution with a volume concentration of 85%, mix and stir for 6 hours, and then adjust the pH to 3 with dilute hydrochloric acid to obtain the modified liquid;

[0049] The irradiation dose of the Teflon particles is 800 KGy, the irradiation time is 8 days, and the particle size of the Teflon particles is 3 μm.

[0050] The preparation method of the pretreated spherical carrier is as follows: add 5% of the mass of the spherical carrier to the aqueous dispersion of the spherical carrier at a concentration of 20g / L, perform ultrasonic dispersion for 25 minutes, centrifuge and dry the resulting components to obtain the pretreated spherical carrier.

[0051] The preparation method of the spherical carrier is as follows: add a 5% volume and 2 mol / L concentration of cerium nitrate aqueous solution to a 10 g / L concentration of porous alumina microsphere aqueous dispersion, disperse evenly by ultrasonication, and then keep the mixture at a temperature of 150°C for 15 hours; after the reaction is completed, naturally cool the product components to room temperature, and wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 4 times after centrifugal separation; after washing is completed, vacuum dry it to obtain a spherical carrier.

[0052] The preparation method of porous alumina microspheres is as follows: aluminum hydroxide and deionized water are mixed in a mass ratio of 1:0.7, and after ball milling, ammonium bicarbonate with a mass ratio of 6% of aluminum hydroxide and 3% of a polyvinyl alcohol aqueous solution with a concentration of 8wt% are added, and the mixture is stirred at a rate of 1500r / min for 80min; the obtained mixed slurry is spray-dried and then calcined at a temperature of 750°C for 2h; after sintering is completed, it is vibrated and sieved to obtain porous alumina microspheres with a particle size of 30μm.

[0053] Example 3

[0054] The preparation method of a wear-resistant and corrosion-resistant polyethylene composite material for rollers provided in this embodiment is basically the same as that in Example 1, except that the specific composition of the wear-resistant and corrosion-resistant polyethylene composite material for rollers and the preparation method of the wear-resistant and corrosion-resistant additive are not completely the same. The specific composition of the wear-resistant and corrosion-resistant polyethylene composite material for rollers and the preparation method of the wear-resistant and corrosion-resistant additive in this embodiment are as follows:

[0055] A wear-resistant and corrosion-resistant polyethylene composite material for rollers, the polyethylene composite material consists of the following raw materials in parts by weight: 80 parts of compound polyethylene, 30 parts of glass fiber, 3 parts of molybdenum disulfide, 8 parts of ammonium polyphosphate, 5 parts of polyethylene wax, 8 parts of nano titanium dioxide, 1.5 parts of graphene, 8 parts of maleic anhydride grafted polyethylene, 1.5 parts of antioxidant 168, 1 part of ultraviolet absorber UV-531, 0.8 part of silane coupling agent KH570 and 5 parts of wear-resistant and corrosion-resistant additives; wherein the compound polyethylene is compounded by high-density polyethylene with a melt index of 18 g / 10 min and high-density polyethylene with a melt index of 0.8 g / 10 min in a mass ratio of 2:1; the glass fiber is alkali-free glass fiber with a diameter of 13 μm.

[0056] The preparation method of the wear-resistant anticorrosion additive comprises the following steps:

[0057] Step 1, ultrasonically dispersing the pretreated spherical carrier in deionized water at a solid-liquid ratio of 60g / L, then adding a grafting agent of 50% of the pretreated spherical carrier, 40% of 3-hydroxy-1,3,5-pentanetriic acid, 1.2% of p-hydroxyanisole, and 2% of ammonium chloride, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 120°C for 20 minutes; after the reaction is completed, filtering, washing and drying the resultant components in turn, and storing the obtained modified spherical carrier for standby use;

[0058] The preparation method of the grafting agent is as follows: chitosan is added into isopropanol at a dosage ratio of 0.05 g / mL, and after ultrasonic dispersion for 50 minutes, trimethyl ammonium chloride glycidyl is added in an amount 5 times the mass of chitosan, and the mixture is mixed and stirred evenly, and then kept warm for reaction at 80°C for 6 hours; after the reaction is completed, the grafting agent is obtained by washing and drying in sequence;

[0059] Step 2: Mix the irradiated modified Teflon particles with 1.2 times the mass of the modified spherical carrier and 5 times the volume concentration of 95% ethanol aqueous solution, stir evenly, heat to 70°C, and then slowly drop 10% of the volume of the modified liquid into the obtained mixed solution; after the dropwise addition is completed, keep the mixture at 70°C for 3 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, and then filter and vacuum dry them in turn to obtain a wear-resistant and anti-corrosion additive;

[0060] The preparation method of the modified liquid is as follows: add 15% of the volume of vinyl trimethoxy silane to a 90% ethanol aqueous solution, mix and stir for 8 hours, and then adjust the pH to 3.5 with dilute hydrochloric acid to obtain the modified liquid;

[0061] The irradiation dose of the Teflon particles is 1000 KGy, the irradiation time is 5 days, and the particle size of the Teflon particles is 2 μm.

[0062] The preparation method of the pretreated spherical carrier is as follows: add 8% of the mass of the spherical carrier to the aqueous phase dispersion of the spherical carrier with a concentration of 30g / L, ultrasonically disperse for 30 minutes, centrifuge and dry the resulting components to obtain the pretreated spherical carrier.

[0063] The preparation method of the spherical carrier is as follows: add a 6% volume and 3 mol / L concentration of cerium nitrate aqueous solution to a 15 g / L concentration of porous alumina microsphere aqueous dispersion, disperse evenly by ultrasonication, and then keep the mixture at 160°C for 20 hours; after the reaction is completed, naturally cool the product components to room temperature, and wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 4 times after centrifugal separation; after washing, vacuum dry the obtained filter cake to obtain the spherical carrier.

[0064] The preparation method of porous alumina microspheres is as follows: aluminum hydroxide and deionized water are mixed in a mass ratio of 1:0.8, and after ball milling, ammonium bicarbonate with a mass ratio of 8% of aluminum hydroxide and 3% of a 10wt% polyvinyl alcohol aqueous solution are added, and the mixture is stirred at a rate of 1500r / min for 90min; the obtained mixed slurry is spray-dried and then calcined at a temperature of 780°C for 2h; after sintering is completed, it is vibrated and sieved to obtain porous alumina microspheres with a particle size of 30μm.

[0065] Comparative Example 1: The main difference between this comparative example and Example 1 is that an equal amount of modified spherical carrier is used in this comparative example to replace the wear-resistant anticorrosion additive.

[0066] Comparative Example 2: The main difference between this comparative example and comparative example 1 is that an equal amount of spherical carrier is used to replace the wear-resistant anticorrosion additive in this comparative example.

[0067] Comparative Example 3: The main difference between this comparative example and comparative example 1 is that in this comparative example, an equal amount of porous alumina microspheres are used to replace the wear-resistant and anti-corrosion additive.

[0068] Performance Testing

[0069] The relevant properties of the wear-resistant and corrosion-resistant polyethylene composite material samples for rollers provided in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively, and the obtained test data were recorded in the following table:

[0070]

[0071] By comparing and analyzing the relevant data in the table, it can be seen that the polyethylene composite material prepared by the present invention not only has excellent wear resistance and mechanical properties, but also has excellent anti-corrosion performance, which prolongs its service life to a certain extent while also ensuring its quality. This shows that the wear-resistant and anti-corrosion polyethylene composite material for rollers and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0072] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0073] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A wear-resistant and corrosion-resistant polyethylene composite material for rollers, characterized in that: The polyethylene composite material is composed of the following raw materials in parts by weight: 50-80 parts of compound polyethylene, 20-30 parts of glass fiber, 2-3 parts of molybdenum disulfide, 4-8 parts of ammonium polyphosphate, 2-5 parts of polyethylene wax, 5-8 parts of nano titanium dioxide, 0.8-1.5 parts of graphene, 5-8 parts of toughening agent, 0.8-1.5 parts of antioxidant, 0.5-1 part of ultraviolet absorber, 0.3-0.8 parts of silane coupling agent and 3-5 parts of wear-resistant and anti-corrosion additives; The compound polyethylene is compounded by high-density polyethylene with a melt index of 18 g / 10 min and high-density polyethylene with a melt index of 0.8 g / 10 min in a mass ratio of 2 to 3:

1.

2. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 1, characterized in that: The toughening agent is selected from any one of maleic anhydride grafted polyethylene, maleic anhydride grafted ethylene-octene copolymer, and maleic anhydride grafted ethylene-vinyl acetate copolymer.

3. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 1, characterized in that: The preparation method of the wear-resistant and anti-corrosion additive comprises the following steps: Step 1, ultrasonically dispersing the pretreated spherical carrier in deionized water at a solid-liquid ratio of 30 to 60 g / L, then adding 30 to 50% of the grafting agent of the pretreated spherical carrier, 20 to 40% of 3-hydroxy-1,3,5-pentanetriic acid, 0.8 to 1.2% of p-hydroxyanisole, and 1 to 2% of ammonium chloride, mixing and stirring evenly, and then heat-retaining and reacting at a temperature of 100 to 120° C. for 20 to 40 minutes; after the reaction is completed, filtering, washing and drying the resultant components in turn, and storing and using the modified spherical carrier; Step 2: Mix the irradiated modified Teflon particles with 0.8 to 1.2 times the mass of the modified spherical carrier and 3 to 5 times the volume of 90 to 95% ethanol aqueous solution, stir evenly, and then heat to 50 to 70° C., and then slowly drop 6 to 10% of the volume of the modified liquid into the obtained mixed solution; after the dropwise addition is completed, keep the mixture at 60 to 70° C. for 2 to 3 hours; after the reaction is completed, naturally cool the obtained product components to room temperature, and then filter and vacuum dry them in turn to obtain a wear-resistant and anti-corrosion additive.

4. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 3, characterized in that: The preparation method of the pretreated spherical carrier is as follows: add 3-8% of the mass of the spherical carrier to a spherical carrier aqueous dispersion with a concentration of 10-30 g / L, perform ultrasonic dispersion for 20-30 minutes, centrifuge and dry the resulting components to obtain the pretreated spherical carrier.

5. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 3, characterized in that: The preparation method of the grafting agent is as follows: chitosan is added into isopropanol at a dosage ratio of 0.02-0.05 g / mL, and after ultrasonic dispersion for 30-50 minutes, trimethyl ammonium chloride glycidyl is added in an amount 3-5 times the mass of chitosan, and after mixing and stirring evenly, the mixture is kept warm at a temperature of 60-80° C. for reaction for 3-6 hours; after the reaction is completed, the mixture is washed and dried in sequence to obtain the grafting agent.

6. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 3, characterized in that: The preparation method of the modified liquid is as follows: add 10-15% of the volume of vinyltrimethoxysilane to an ethanol aqueous solution with a volume concentration of 80-90%, mix and stir for 5-8 hours, and then adjust the pH to 3-3.5 with dilute hydrochloric acid to obtain the modified liquid.

7. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 3, characterized in that: The irradiation dose of the Teflon particles is 500-1000 KGy, the irradiation time is 5-10 days; and the particle size of the Teflon particles is 2-5 μm.

8. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 4, characterized in that: The preparation method of the spherical carrier is as follows: add a cerium nitrate aqueous solution with a volume of 3% to 6% and a concentration of 2 to 3 mol / L to a porous alumina microsphere aqueous phase dispersion with a concentration of 5 to 15 g / L, disperse uniformly by ultrasonication, and then keep the mixture in a temperature of 120 to 160° C. for reaction for 10 to 20 hours; after the reaction is completed, naturally cool the resultant components to room temperature, and wash the obtained filter cake alternately with deionized water and anhydrous ethanol for 3 to 4 times after centrifugal separation; after washing is completed, vacuum dry the obtained filter cake to obtain the spherical carrier.

9. The wear-resistant and corrosion-resistant polyethylene composite material for rollers according to claim 8, characterized in that: The preparation method of the porous alumina microspheres is as follows: aluminum hydroxide and deionized water are mixed at a mass ratio of 1:0.6-0.8, and after ball milling, ammonium bicarbonate with a mass of 3-8% of aluminum hydroxide and 2-3% of a polyvinyl alcohol aqueous solution with a concentration of 6-10wt% are added, and the mixture is stirred at a speed of 1200-1500 r / min for 60-90 minutes; the obtained mixed slurry is spray-dried and then calcined at a temperature of 730-780°C for 1-2 hours; After sintering is completed, the product is vibrated and sieved to obtain porous alumina microspheres with a particle size of 25 to 45 μm.

10. A method for preparing the wear-resistant and corrosion-resistant polyethylene composite material for rollers according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: accurately weighing various raw materials required for preparing the polyethylene composite material, and putting them into a high-speed stirring device, mixing and stirring them evenly, and transferring the obtained mixed material into a twin-screw extruder for basic granulation, and the obtained material is the wear-resistant and corrosion-resistant polyethylene composite material for rollers; The parameters of twin-screw extrusion are set as follows: the temperature of the first section is 180-200°C, the temperature of the second to tenth sections is 200-240°C; the head temperature is 235°C, the main engine speed is 350-500rpm, and the feeding rate is 30-50rpm.

Citation Information

Patent Citations

  • Graphene modified high-density polyethylene composite material for carrier roller and preparation method of graphene modified high-density polyethylene composite material

    CN112961420A

  • Antibacterial PVC decorative film and preparation method thereof

    CN118895012A

  • Polyethylene-based resin composition

    JP2023026074A